Physical quality of an Oxisol cultivated with maize submited to cover crops in the pre-cropping period - Pereira, Fabiana de Souza [UNESP]; Andrioli, Itamar [UNESP]; Beutler, Amauri Nelson; de Almeida, Cinara Xavier [UNESP]; Pereira, Faber de Souza (Sociedade Brasileira de Ciência do Solo, 2010)
The intensive use of land alters the distribution of the pore size which imparts consequences on the soil physical quality. The Least Limiting Water Range (LLWR) allows for the visualization of the effects of management systems upon either the improvement or the degradation of the soil physical quality. The objective of this study was to evaluate the physical quality of a Red Latosol (Oxisol) submited to cover crops in the period prior to the maize crop in a no-tillage and conventional tillage system, using porosity, soil bulk density and the LLWR as attributes. The treatments were: conventional tillage (CT) and a no-tillage system with the following cover crops: sunn hemp (Crotalaria juncea L.) (NS), pearl millet (Pennisetum americanum (L.) Leeke) (NP) and lablab (Dolichos lablab L.) (NL). The experimental design was randomized blocks in subdivided plots with six replications, with the plots being constituted by the treatments and the subplots by the layers analyzed. The no-tillage systems showed higher total porosity and soil organic matter at the 0-0.5 m layer for the CT. The CT did not differ from the NL or NS in relation to macroporosity. The NP showed the greater porosity, while CT and NS presented lower soil bulk density. No <= 10 % airing porosity was found for the treatments evaluated, and value for water content where soil aeration is critical (theta(PA)) was found above estimated water content at field capacity (theta(FC)) for all densities. Critical soil bulk density was of 1.36 and 1.43 Mg m(-3) for NP and CT, respectively. The LLWR in the no-tillage systems was limited in the upper part by the theta(FC), and in the bottom part, by the water content from which soil resistance to penetration is limiting (theta(PR)). By means of LLWR it was observed that the soil presented good physical quality.

O uso intensivo do solo modifica a distribuição do tamanho de poros, com reflexos na qualidade física do solo. O intervalo hídrico ótimo (IHO) permite visualizar os efeitos dos sistemas de manejo na melhoria ou na degradação da qualidade física do solo. Objetivou-se, com este estudo, avaliar a qualidade física de um Latossolo Vermelho submetido a culturas de plantas de cobertura em pré-safra ao milho, em sistema de semeadura direta e em sistema convencional, utilizando como atributos a porosidade, a densidade do solo e o IHO. Os tratamentos foram: plantio convencional (PC) e sistema de semeadura direta com as seguintes plantas de cobertura: crotalária (Crotalaria juncea L.) (SC), milheto (Pennisetum americanum (L.) Leeke) (SM) e lab lab (Dolichos lablab L.) (SL). O delineamento experimental foi o de blocos casualizados em parcelas subdivididas, com seis repetições, sendo as parcelas constituídas pelos tratamentos e as subparcelas pelas camadas analisadas. O cultivo do solo em sistema de semeadura direta apresentou maior valor de porosidade total e conteúdo de matéria orgânica na camada de 0–0,05 m em relação ao PC. Este não diferiu do SL e do SC quanto à macroporosidade. O SM apresentou maior microporosidade. O PC e o SC apresentaram menor densidade do solo. Não houve porosidade de aeração < 10 % nos tratamentos avaliados, e o valor do conteúdo de água no solo em que a porosidade de aeração é crítica (θ PA) manteve-se acima do conteúdo de água estimado na capacidade de campo (θ CC), para todas as densidades. A densidade do solo crítica foi de 1,36 e 1,43 Mg m-3 para SM e PC, respectivamente. Os IHOs nos sistemas de semeadura direta foram limitados na parte superior pelo θ CC e, na parte inferior, pelos valores de conteúdo de água em que a resistência do solo à penetração atinge valores críticos (θRP). Verificou-se por meio do IHO que o solo apresentou boa qualidade física.
Qualidade física de um Latossolo vermelho cultivado com milho submetido a culturas de plantas de cobertura em pré-safra
Keywords: Management systems; Physical attributes; least limiting water range